2003
DOI: 10.1063/1.1540231
|View full text |Cite
|
Sign up to set email alerts
|

Remanent polarization of evaporated films of vinylidene fluoride oligomers

Abstract: A remanent polarization of 130Ϯ3 mC/m 2 , large among the values reported for organic materials, and rectangular D -E hysteresis curves were realized in synthesized vinylidene fluoride ͑VDF͒ oligomer ͓CF 3 (CH 2 CF 2 ) 17 I͔ film evaporated onto a platinum surface around liquid nitrogen temperature. The results suggested that the VDF oligomer film has an extremely high crystallinity, and the electric dipoles arrange almost perfectly perpendicular to the film surface, and that a Lorentz local field factor of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 30 publications
1
68
2
Order By: Relevance
“…at 123 K under a vacuum of 10 À5 Pa to ensure that the VDF telomers were in a ferroelectric state (form I) and that the axis of the molecular chain was oriented parallel to the substrate. 8,9 The thickness of the VDF telomer and the Al electrodes was controlled at 300 and 50 nm, respectively. Stacks of Al/VDF telomer/Al acted as the capacitor, and the charge was proportional to the stress applied to the film.…”
Section: Iodine Transfer Polymerization Of Vdf and Ethylene Endcappingmentioning
confidence: 99%
See 1 more Smart Citation
“…at 123 K under a vacuum of 10 À5 Pa to ensure that the VDF telomers were in a ferroelectric state (form I) and that the axis of the molecular chain was oriented parallel to the substrate. 8,9 The thickness of the VDF telomer and the Al electrodes was controlled at 300 and 50 nm, respectively. Stacks of Al/VDF telomer/Al acted as the capacitor, and the charge was proportional to the stress applied to the film.…”
Section: Iodine Transfer Polymerization Of Vdf and Ethylene Endcappingmentioning
confidence: 99%
“…Among organic ferroelectrics, CF 3 (VDF) 17 I possesses a relatively high remanent polarization. 9 Furthermore, previous experiments on CF 3 (VDF) 13.4 C 2 H 5 revealed that the piezoelectric coefficient of VDF telomers was greater than that of oligo(VDF-co-TrFE) copolymers, and a thinner and more uniform film could be obtained. 6,7 The objective of this study was to design various VDF-based telomers, such as C n F 2n+1 (VDF) p -(C 2 H 4 ) x -X (where n¼4 or 6; p¼6-23; x¼0, 1 and X¼H or I), and to alter the crystallinity, ferroelectric and piezoelectrical properties by controlling the number of VDF units and end groups.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained value of E c of about 0.6 MV/m (supplementary material, Sec. IV) 28 is two to three orders of magnitude lower than the previously reported values for VDF oligomers (100-200 MV/m), 21 and at least an order of magnitude lower than the lowest coercive field reported for the PVDF-TrFE nanostructures (of order 10 MV/m). 31 The coercive field value obtained from analysis of the PFM images is in good agreement with the macroscopic currentvoltage measurements (Fig.…”
mentioning
confidence: 41%
“…In our case, molecular chains are oriented nearly normal to the substrate and thus each molecular chain has a smaller interaction cross-sectional area at the interface (substrate) than the in-plane oriented molecular chains. This provides a relatively large degree of freedom for the dipole rotation (less steric hindrance 21 ) resulting in the low coercive field value.…”
mentioning
confidence: 99%
See 1 more Smart Citation